Analysis Factors Which Influence Students Make a Visit to Cafe in City Padang - Dinda Jumaisha; Waryono (Journal of Multidimensional Management, 2025)
This research is motivated by the phenomenon of the proliferation of cafes in Padang City, which has led to an increase in the culture of hanging out and visiting cafes among students in Padang City. Cafes no longer provide consumption needs but have become useful social spaces. The purpose of this study is to determine the factors that influence students to visit cafes in Padang City. This study uses a qualitative method with a phenomenological approach. Data were collected through observation, documentation, and interviews. Data analysis techniques in this study include four stages: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are cultural, social, personal and psychological factors that influence students in visiting cafes in Padang City. The dominant factors are psychological and social factors because students visit cafes to create emotional comfort and fulfill social interactions.